Cardiаc involvement by COVID-19 in children: retrospective analysis of 10 cases and literature review - Zornitsa Vassileva; Anna Kaneva; Anna Dasheva; Kameliya Genova (Българска кардиология, 2022)
Cardiac involvement by COVID-19 in children occurs most often as a part of the multisystem inﬂ ammatory syndrome by children (MIS-C) and rarely as an isolated ﬁ nding; affected children are predominantly older males. We present retrospective analysis data of 10 children with myocardial involvement within COVID-19, who were admitted at the Pediatric Cardiology Department of the National Heart Hospital – Soﬁ a. The main clinical symptoms were fever, heart failure, and gastrointestinal complaints, and the typical laboratory constellation included pronounced leukocytosis with extreme granulocytosis, signiﬁ cant elevation of inﬂ ammatory markers, increased serum troponin levels, and serologic evidence of contact with SARS-CoV2. Chest X-ray showed cardiomegaly and pulmonary hypervolemia; ECG changes were diverse and included abnormal repolarization and rhythm and conduction disturbances. Echocardiography revealed left ventricular dilation with depressed contractility, and cardiac MRI demonstrated myocardial edema and necrosis. Following immunomodulatory treatment, rapid recovery was observed. However, in most cases, the MRI changes persisted 6 months after the onset of symptoms, which makes the long-term prognosis unclear. We have reviewed our results considering the recent publications in the international databases regarding cardiac involvement by COVID-19 in children.